The Role of Teachers in Monitoring Islamic Education Learning Attainment in Madrasahs - Mita Wahyuni (Yayasan Bayt Shufiya Nusantara, 2026)
The gap between the mastery of religious theory and the implementation of practical morality constitutes a major challenge in Islamic Education (PAI) learning at the madrasah level. This study aims to analyze the teacher monitoring system regarding the achievement of PAI learning through mentoring activities at MTs Ulumul Qur'an Medan, while simultaneously identifying multisectoral obstacles and their strategic solutions. The method employed is qualitative with a descriptive qualitative design. Primary data were gathered through non-participant observation and in-depth interviews with the Principal, PAI teachers, and a sample of eighth-grade students, whereas secondary data were extracted through documentation studies and literature reviews encompassing data reduction, data display, and conclusion drawing. The findings indicate that the monitoring of PAI learning achievement is realized through the reconstruction of five adaptive mentoring stages, namely cognitive grounding, behavioral habituation, deep value internalization, sense of need autonomy, and continuous quality improvement. This embedded monitoring system is proven to effectively mitigate the madrasah's multisectoral obstacles, such as weaknesses in students' initial input competence, constraints in teachers' supervision time and space, and asymmetric support from the family environment. This collaborative approach successfully transforms students' religious behavior, with the success rate characterized by independent worship (awareness of congregational dhuha and dhuhur prayers), reinforcement of a culture of politeness, and preventive effectiveness against student delinquency. The socio-pedagogical implication of this research emphasizes that the synergy of small-group-based monitoring (halaqah) is highly essential to shift students' moral obedience from heteronomous to autonomous, while simultaneously providing a tactical model for madrasah administrators in optimizing the quality of learners' spiritual character in the globalization era.